Implementing the teaching/learning of oral skills in secondary education in Aragón: Gauging teachers’ attitudes, beliefs and expectations - Plo, Ramón; Hornero, Ana; Mur Dueñas, Pilar (International Journal of English Studies, 2014)
Current national curricula, the Common European Framework of Reference for Languages, and EFL materials highlight the importance of the students’ development of oral skills. This study stems from a cross-sectional survey of the teaching of oral skills in Secondary Education in a Spanish local context (Aragón) carried out in 2012 on both teachers and students of English. The present paper focuses on the answers obtained from the group of teachers in order to provide a snapshot of their attitudes, beliefs and expectations regarding the teaching, learning and assessment of oral skills, as well as the implementation of some measures aimed at increasing the required level of oral competence in the foreign language. Teachers’ answers reveal that in spite of what is indicated in language policies, oral skills are not sufficiently practiced and/or assessed; that students are still reluctant to engage in oral activities and do not, therefore, reach the required level in these skills. doi: http://dx.doi.org/10.6018/ijes/14/1/175041